Mandibular ramus distraction osteogenesis and Lefort I osteotomy for obstructive sleep apnea: A case report monitored with home respiratory polygraphy - Galder Hernando Martín; Pilar Rubio-Bueno; Ana Martínez Gil-Ortega; Joaquín Durán-Cantolla (Oral and Maxillofacial Surgery Cases)
A new monitoring protocol for orthognathic surgery for addressing obstructive sleep apnea syndrome in adult patients using bilateral internal ramus distraction (BIRD) followed by Lefort I osteotomy and monitored by HRP is presented. This strategy is part of an outpatient major surgery protocol and includes preoperative 3d virtual planning, followed by surgery under general anesthesia with endoscopic assistance.Following the procedure, patients are typically discharged on the same day, with the vertical lengthening of the mandibular ramus starting after a 5-day period and progressing at a speed of 0.5–1 mm per day over a period of 10–50 days. The process carries on until the negative dental overjet exceeds 10 mm or the apnea-hypopnea index falls beneath 15 events per hour, demonstrating a curative level.Mandibular advancement monitorization based on clinical, polygraphic, or polysomnographic criteria enables the surgeon to meet the individual needs of each patient. The distractors are typically maintained in position for six months following elongation of 10–25 mm to ensure proper consolidation.BIRD followed by LeFort I osteotomy, has demonstrated significant efficacy as a treatment for obstructive sleep apnea syndrome in adult patients, irrespective of the presence of retrognathia. Furthermore, this approach may offer particular advantages for patients with severe cardiovascular disease or diabetes.